S15.2 European gonococcal antimicrobial surveillance programme (Euro-GASP): towards timelier monitoring. (10th July 2011) - Cole, M J; Chisholm, S A; Unemo, M; Hoffmann, S; van de Laar, M J W; Ison, C A
Abstract : Background: It is imperative that antimicrobial resistance (AMR) surveillance systems work in a timely manner and outcomes are translated into treatment guidelines without delay. For the first time in 2010, the European gonococcal antimicrobial surveillance programme (Euro-GASP) introduced biannual testing to allow more frequent reporting of trends and developments in Neisseria gonorrhoeae AMR across Europe. Methods: In the first half of 2010, 18 out of the 30 EU/EEA Member States contributed up to 55 consecutive gonococcal isolates to Euro-GASP. Susceptibility testing was performed by Etest or agar dilution for therapeutically relevant antimicrobials: azithromycin, cefixime, ceftriaxone, ciprofloxacin, gentamicin and spectinomycin. Biannual testing continued into the second half of 2010. Additionally 10 laboratories performed decentralised testing with the submission of AMR data into Euro-GASP instead of gonococcal isolates. Results: In the first round of biannual testing 900 N gonorrhoeae isolates were tested. Eight per cent of the isolates displayed decreased susceptibility (>0.125 mg/l) to cefixime, which was an increase from 5% in 2009. No decreased susceptibility to ceftriaxone was detected. For ciprofloxacin, the overall incidence of resistant isolates decreased from 63% in 2009 to 52% in 2010 and azithromycin resistance decreased from 13% in 2009 to 5% in 2010. No resistance to spectinomycin was demonstrated. The MIC50 and MIC90 of gentamicin in the isolates remained at 8 mg/l in 2010. Conclusions: The results from the first round of biannual testing have shown that isolates displaying decreased susceptibility to cefixime are rapidly increasing. This is a major concern as cefixime is a widely used, recommended therapy for gonorrhoea across Europe. Healthcare professions should be aware of cefixime treatment failures, particularly in light of the recent identification of treatment failures in Norway and the UK. The MICs of ceftriaxone need to be monitored continually to preserve this precious treatment option. Euro-GASP is currently being adjusted to allow for timely reporting and decentralised testing including representativeness and links to epidemiological data. All of which contribute to monitoring the ever changing gonococcus in timelier and more efficient ways, with the ultimate aim of treating infected individuals successfully.